Application of an organoid-based model to explore Helicobacter pylori–human gastric epithelium interaction in vitro - Yu, Byeong Min; Lee, So Dam; Hwang, Bo Ram; Kim, Ji Seon; Yu, Sungsook; Nam, Ki Taek; Lee, Yong Chan (Frontiers in Cellular and Infection Microbiology, 2025)
Helicobacter pylori infection causes histopathologic changes in gastric epithelial cells, resulting in conditions such as gastritis, gastric ulcers, and ultimately, gastric cancer. To date, various experimental models, including cell lines and animal studies, have been employed to investigate these pathological processes. However, each model presents its limitations. This study compared the re-cultured three-dimensional organoids from infected single cells, apical-out, and two-dimensional (2D) organoids models to better understand the mechanisms underlying the epithelial changes caused by H. pylori infection in the human stomach. Thus, we analyzed the epithelial cell responses, inflammatory mediator expressions, apical-junctional complex alterations, and H. pylori infection interactions in these organoid models. Moreover, we revealed that the high accessibility and experimental efficiency of the apical-out and 2D models enable easier manipulation and faster analysis of H. pylori infection compared to the single-cell infection model. These results indicate the potential of various organoid models in H. pylori infection studies to provide essential data that help in understanding the mechanisms of epithelial changes and in developing new therapeutic strategies for gastric pathology.